The Effect of Psychosocial Self-Care Education on Retirement Syndrome in Educators: A Quasi-experimental Study - Fatemeh Mardani Chamazkotih; Hossein Ajam Zibad; Leila Sadeghmoghadam (University of Social Welfare & Rehabilitation Sciences, 2022)
Objectives Retirement is one of the life crises which can cause psychological and social problems in people and cause incompatibility and symptoms called Retirement Syndrome. This study aimed to investigate the effect of the psychosocial self-care training program on retirement syndrome in educators as a program to improve and expose retirees to retirement.  Methods & Materials In this study, a two-group quasi-experimental method was performed on 64 education retirees in 1398 in Gonabad. After reviewing the entry and exit criteria of the research units (individuals were randomly assigned), they were assigned to two experimental and control groups. Psychosocial self-care training sessions were held once a week for 6 hours for one hour (for) the intervention group. The participants completed the retirement syndrome questionnaire at the beginning and end of these sessions. After data collection, the analysis was performed using SPSS software v. 20. The significance level was considered at P<0.05. Results This study considered 4 main categories regarding retirement syndrome. These categories include Feelings of confusion and conflict, Feelings of new effort and orientation, Feelings of old age and emptiness, and feelings of helplessness and failure. Also, based on the independent t-test, no statistically significant difference was observed between the retirement syndrome scores of the two groups before the intervention (P>0.05); however, the average score of retirement syndrome in the two groups after the intervention and the difference in the average score of retirement syndrome of the two groups before and after the intervention had a statistically significant difference (P<0.05). This means that the training program improved the intervention group's retirement syndrome (P<0.05). Conclusion The results of the current study showed that holding face-to-face meetings and conducting psychosocial self-care training on retirement syndrome in retired educators positively reduced the symptoms of retirement syndrome. By teaching self-care and learning self-care strategies in old age, we can prepare retirees to cope with or reduce the symptoms of retirement syndrome.